The impact of relaxation of methadone take-home protocols on treatment outcomes in the COVID-19 era. (2nd November 2021) - Amram, Ofer; Amiri, Solmaz; Panwala, Victoria; Lutz, Robert; Joudrey, Paul J.; Socias, Eugenia
ABSTRACT: Background: Background: In response to the COVID-19 pandemic, the US Substance Abuse and Mental Health Services Administration (SAMHSA) allowed for an increase in methadone take-home doses for the treatment of Opioid Use Disorder (OUD) in March 2020. Objective: To evaluate the effects of the SAMSHA exemption on methadone adherence and OUD-related outcomes. Methods: A convenience sample of 183 clients (58% female) were recruited from a methadone clinic in the fall of 2019 for a cross-sectional survey. Survey data was linked to clinical records, including urine drug testing (UDT) results for methadone and emergency department (ED) visits at the local hospital. Participants were on stable methadone dosing for 9 months prior to and following March 2020. Methadone adherence was assessed by UDTs; OUD-related outcomes were assessed by overdose events and ED visits. Logistic regression was used to assess the association between change in take-home methadone doses and outcomes. Results: Mean take-home doses increased nearly 200% (11.4 doses/30 days pre-COVID-19 vs. 22.3 post-SAMHSA exemption). ED visits dropped from 74 (40.4%) pre-COVID-19 to 56 (30.6%) post-SAMHSA exemption ( p = <0.001). No significant changes were observed in either the number of clients experiencing overdose or those who experienced one or more methadone negative UDTs in the post-SAMHSA exemption period. Adjusted models did not show a significant association between changes in take-home doses and associated outcomes. Conclusions: Despite a near-doubling of take-home methadone doses during the COVID-19 exemption period, the increase in take-home doses was not associated with negative treatment outcomes in methadone-adherent clients.